(untitled) (Journal of Engineering, 2007)
A novel method in induction heating is presented. The winding of the excitation coil is helical and of three – phase type while the charge is cylindrical. This heating system is compared with the classical induction heating system of the circular coil type with cylindrical charge and single – phase excitation. The study shows the merits of the proposed new system over the conventional one. The multi – layer theory approach is adopted for the analysis of helical winding induction heating system which is an analytical method.